Software-defined radio-based HF doppler receiving system - Hiroyuki Nakata (SpringerOpen, 2021)
Abstract High-frequency Doppler (HFD) sounding is one of the major remote sensing techniques used for monitoring the ionosphere. Conventional systems for HFDs mainly utilize analog circuits. However, existing analog systems have become difficult to maintain as the number of people capable of working with analog circuits has declined. To solve this problem, we developed an alternate HFD receiver system based on digital signal processing. The software-defined radio (SDR) technique enables the receiver to be set up without the knowledge of analog circuit devices. This approach also downsizes the system and reduces costs. A highly stabilized radio system for both the transmitter and receiver is necessary for stable long-term observations of various phenomena in the ionosphere. The global positioning system disciplined oscillator with an accuracy of $${10}^{-11}$$ 10 - 11 compensates for the frequency stability required by the new receiving system. In the new system, four frequencies are received and signal-processed simultaneously. The dynamic range of the new system is wider (> 130 dB) than that of the conventional system used in HFD observations conducted by the University of Electro-Communications in Japan. The signal-to-noise ratio significantly improved by 20 dB. The new digital system enables radio waves to be received with much smaller amplitudes at four different frequencies. The new digital receivers have been installed at some of the stations in the HFD observation network in Japan and have already captured various ionospheric phenomena, including medium-scale traveling ionospheric disturbances and sudden commencement induced electric field fluctuations, which indicates the feasibility of SDR for actual ionospheric observations. The new digital receiver is simple, inexpensive, and small in size, which makes it easy to deploy new receiving stations in Japan and elsewhere. These advantages of the new system will help drive the construction of a wide HFD observation network. Graphical Abstract